The UJI EFIKASI BIOFUNGISIDA BAHAN AKTIF Streptomyces sp DAN Geobacillus sp. TERHADAP INTENSITAS PENYAKIT BERCAK UNGU PADA BAWANG MERAH (Allium ascalonicum L): shallot , biofungicide, Streptomyces, Geobacillus , Alternaria porri. - Hadi, Pramono; Toni, Toni; Juli Rachmawatie, Srie; Mukti P, Shalahudin (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2022)
ABSTRACT Shallots (Allium ascalonicum L.) is a leading vegetable commodity in Indonesia which is cultivated in an incentive by farmers. The development of shallot farming in Indonesia is directed at increasing yields, quality of production and income as well as improving the standard of living of farmers. Loss of shallot production can not be separated from the effect of increasing or decreasing the attack of plant pests and diseases. This study aims to determine the concentration of the biofungicide active ingredient Streptomyces sp 1 x 106 cfu/gram and Geobacillus sp 1 x 106 cfu/gram The most effective for controlling purple spot disease on shallots . This research was carried out from November 2021 to January 2022 in Wonodoyo Village, Cepogo District, Boyolali Regency at an altitude of 1,300 masl with brown lithosol soil type. The method used in this study was a non-factorial Completely Randomized Block Design (CRBD) with 5 (five) different biofungicide concentrations. The concentration treatment used is 1.5 gr / liter ( E1 ), 1,25 gr / liter ( E2 ), 1,0 gr / liter ( E3 ), 0,75 gr / liter ( E4 ), and farmer treatment ( E0 ). The results showed that the concentration treatment of the biofungicide active ingredient Streptomyces sp 1 x 106 cfu/gram and Geobacillus sp 1 x 106 cfu/gram gives a very real influence on the parameters of attack intensity Alternaria porri , weight of wet stover, weight of dry stover, weight of dry tuber, and number of leaves . However, it had no significant effect on plant height parameters. The level of effectiveness of the biofungicide active ingredient Streptomyces sp 1 x 106 cfu/gram and Geobacillus sp 1 x 106 cfu/gram on attack intensity parameter The best Alternaria porri was treated with a concentration of 1,50 gr /liter ( E1 ), with an efficacy level of 76.19 %. Keywords: shallot , biofungicide, Streptomyces, Geobacillus , Alternaria porri.